Dinamika Sosial-Budaya dalam Pendidikan Islam di Indonesia dan ASEAN: Sebuah Systematic Literature Review: Dinamika Sosial-Budaya dalam Pendidikan Islam di Indonesia dan ASEAN: Sebuah Systematic Literature Review - Cahyudi Prima; Isrun Abdurahman; Adang Hambali (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2026)
This study aims to map the influence of socio-cultural factors on the practices and policies of Islamic Education in Indonesia and ASEAN countries. The method used is a Systematic Literature Review (SLR) following the PRISMA protocol. Literature searches were conducted on Connected Papers and Google Scholar databases using selected keywords. Out of 120 identified articles, 10 met the inclusion criteria for in-depth analysis. The findings reveal three main results. First, there are three models of state-Islamic education relations in ASEAN: national integration (Malaysia, Brunei), massive institutionalization (Indonesia), and limited accommodation (Thailand, Philippines, Singapore). Second, local values such as gotong royong in Indonesia, Malay customs in Malaysia-Brunei, izzah in Pattani, and pragmatism in Singapore serve as the moral foundation of Islamic education. Third, common challenges include the tradition-modernity dialectic, digital crisis of scholarly authority, stigma against madrasah graduates, and policy implementation gaps. This study contributes to developing Islamic education policies that are responsive to ASEAN's socio-cultural diversity.